Development of healthy food products: incorporation of seaweeds - Abreu, Raquel Ferreira (2019)
Seaweeds are an excellent source of bioactive nutrients and phytochemicals associated with the prevention of various diseases, contributing to the promotion of healthy and balanced diets. Although their consumption at European level is low compared to Asian countries, they are increasingly being used as a functional ingredient to nutritionally enrich various foods while inducing new eating habits. The objective of this work is to incorporate the brown seaweed Fucus vesiculosus and the green seaweed Ulva rigida, in soups with added value. It is further noted that this objective intended that the formulated soups had sufficient nutritional composition to replace a meal, particularly for the elderly, and should also be organoleptically similar to a traditional Portuguese soup. For this, two different soups were developed, namely one with sweet potato, carrot, pumpkin, zucchini, leek, chickpeas, onion, olive oil, water, salt and a water-soluble soybean extract and being fortified with Fucus vesiculosus in dry basis, and another one containing sweet potato, carrot, pumpkin, zucchini, leek, chickpeas, broccoli, olive oil, water, salt and Ulva rigida in dry base, without the presence of water-soluble extract of soybean. For each one of the soups was designed a control, which consisted of a soup with all ingredients except seaweed. In order to understand possible nutritional and functional benefits, the seaweed-fortified and control soups were analyzed for physical and chemical properties such as color, pH, titratable acidity and nutrients such as relative humidity, protein content, dietary fiber, total and reducing sugars, ash content and elemental composition (minerals). In addition, phytochemical analyzes such as the evaluation of total phenolic compounds and antioxidant activity, as well as the quantification of pigments and carotenoids were carried out. The incorporation of the seaweeds in the soups was notorious at the level of the elemental composition of them. It is important to emphasize the increase of Fe, Mg and Ca in both, as well as the decrease of Na, which is positive because nowadays daily diets are extremely rich in Na. In addition, it was concluded that the soups had the nutritional values that fit the required values of a meal for an elderly person.